PEMANFAATAN MEDIA SOSIAL UNTUK EFEKTIFITAS KOMUNIKASI - Ahmad Setiadi (Universitas Bina Sarana Informatika, 2016)
The phenomenon of social media presence as a result of the development of information andcommunication technology is remarkable. With a variety of services that can be used, social media haschanged the way we communicate in society. Social media presence even had an impact in the way wecommunicate in all fields, such as marketing communication, political communication andcommunication in the learning system. It is certainly interesting to study whether social media presenceonly brings change impacts of conventional means of communication into a modern and all-digital, oralso cause the communication is more effective.Keywords : Social media, effetiveness, communications